Revealing the key modules and potential prognostic markers of gastric cancer transformation based on weighted gene co-expression networks - Li, Heng; Li, Wen; Yang, Zhen; Liu, Haiyu; Zhang, Xiaoping; Zhao, Yufeng; Gu, Hao (Frontiers in Genetics, 2025)
BackgroundThis study aims to identify key modules and targets during the transition from gastric precancerous lesions to gastric cancer by performing weighted gene co-expression network analysis (WGCNA) on gene microarray datasets from the Gene Expression Omnibus (GEO) database containing gastritis, gastric cancer and precancerous lesions, providing insights for early intervention in gastric cancer.MethodsTranscriptomic data from precancerous lesions (including low-grade and high-grade intraepithelial neoplasia) and early gastric cancer were analyzed using differential gene analysis, WGCNA, and survival analysis. Critical modules and genes associated with disease progression were identified. The prognostic value and expression changes of these genes were evaluated, and their expression patterns across disease states were validated in external datasets to confirm key genes involved in the inflammation-cancer transformation into gastric cancer.ResultsWGCNA identified four key modules: pink, purple, red, and magenta. The first three modules were most strongly associated with low-grade intraepithelial neoplasia, high-grade intraepithelial neoplasia, and early gastric cancer, respectively, while magenta was linked to all three stages. Functional analysis reveals: Pink module: Enriched in inflammation-related pathways. Purple module: Involved in chemical carcinogenesis and beta-alanine metabolism. Red module: Associated with immune response and inflammation, participating in NF-kappa B and Toll-like receptor signaling pathways. Magenta module: Linked to complement activation and immune response, enriched in cytokine-cytokine receptor interaction and chemokine signaling pathways. Core genes are filtered based on gene significance (GS > 0.2) and module membership (MM > 0.8). Among 20 shared core genes across disease stages, 13 genes (e.g., FCRL3,EFEMP1,ANKRD29,STOX2) were identified as unfavorable prognostic factors for gastric cancer. External validation confirmed consistent expression patterns of these genes in training and validation datasets, with all four genes (FCRL3, EFEMP1, ANKRD29, STOX2) significantly correlating with poor prognosis.ConclusionWGCNA reveals modules associated with gastric precancerous lesions and cancer progression. FCRL3, EFEMP1, ANKRD29, and STOX2 may serve as potential biomarkers for monitoring the transition from precancerous lesions to gastric cancer, offering insights into the mechanisms of gastric carcinogenesis and supporting early diagnosis and intervention strategies.